Manajemen Konflik dalam Keluarga Sebagai Upaya Mewujudkan Keharmonisan Rumah Tangga - Septiani, Anidha Lingga; Achdiani, Yani (CV. ITTC INDONESIA, 2026)
Marriage is a bond of body and soul aimed at forming a harmonious family (sakinah, mawaddah, wa rahmah), yet differences in personality and external pressures often trigger conflicts. This qualitative study, employing a literature review method, aims to identify conflict-triggering variables, describe constructive resolution strategies, and analyze the correlation between the implementation of POAC and domestic stability. The results of the analysis indicate that conflict management is not merely about suppressing disputes, but rather a conscious process of managing resources and communication. The use of integration strategies and the application of planning, organizing, directing, and controlling functions have proven to be vital instruments in preventing destructive escalation and achieving sustainable harmony